Intensifying Reading Instruction for Students With Attention-Deficit/Hyperactivity Disorder: Practices to Support Classroom Instruction and Family–School Collaboration. (April 2020) - Roberts, Garrett J.; Miller, Gloria E.; Watts, Gavin W.; Malala, Dina K.; Amidon, Brigette E.; Strain, Phil
Many students with attention-deficit/hyperactivity disorder (ADHD) also have reading deficits. These reading deficiencies in students with ADHD are likely to be more severe than those of students with only reading difficulties. To intensify reading instruction to improve reading and behavioral outcomes for students with ADHD, this article describes research-based practices which can be integrated into the classroom reading instruction as well as foster family–school collaboration.